Damage index fragility assessment of low-rise light-frame wood buildings under long duration subduction earthquakes. (May 2020) - Pan, Yuxin; Ventura, Carlos E.; Tannert, Thomas
Highlights: Damage fragility curves for low-rise wood constructions were developed by using IDA. Effects of long duration subduction earthquakes on four wood buildings were quantified. Correlations of duration with structural damage were investigated at various intensity levels. Exterior stucco can be used as an effective retrofit strategy for non-engineered wood buildings. Abstract: This paper presents fragility curves for conventional low-rise light-frame wood buildings in southwestern British Columbia, Canada, for long duration subduction earthquakes. Computational models of four representative two-story houses (two engineered and two non-engineered) are developed and validated using full-scale shake table testing data. Damage states are evaluated using the Park and Ang damage index. Incremental dynamic analyses are employed for calibrating and assessing the index. Duration effects are investigated by using 30 long duration subduction motions and 30 "spectrally equivalent" short duration crustal motions. The results indicate that the considered houses are more vulnerable to damage under subduction motions which increase the median damage indices of both individual shearwalls and entire lateral systems for all four houses at the same level of ground shaking. The correlation between system damage indices with ground motion duration was dependent on the level of ground shaking and the seismic resistance of the systems. The results further demonstrate that exterior stucco finish greatly reduces the seismic damage and can be used as an effective seismic retrofit strategy for conventional non-engineered wood construction.